The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1042/bsr20170286
|View full text |Cite
|
Sign up to set email alerts
|

Dietary capsaicin and its anti-obesity potency: from mechanism to clinical implications

Abstract: Obesity is a growing public health problem, which has now been considered as a pandemic non-communicable disease. However, the efficacy of several approaches for weight loss is limited and variable. Thus, alternative anti-obesity treatments are urgently warranted, which should be effective, safe, and widely available. Active compounds isolated from herbs are similar with the practice of Traditional Chinese Medicine, which has a holistic approach that can target to several organs and tissues in the whole body. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(91 citation statements)
references
References 68 publications
0
82
0
1
Order By: Relevance
“…Lifestyle change including dietary interventions and physical activity is regarded as an inevitable part of obesity treatment strategies (Swift, Johannsen, Lavie, Earnest, & Church, ). Although reduced dietary energy intake is an important part of weight‐reducing diets, a number of studies have revealed that including functional foods like cinnamon, ginger, pepper, cumin, and garlic (Ebrahimzadeh Attari, Ostadrahimi, Asghari Jafarabadi, Mehralizadeh, & Mahluji, ; Gupta Jain, Puri, Misra, Gulati, & Mani, ; Szulinska et al, ; Zare, Heshmati, Fallahzadeh, & Nadjarzadeh, ; Zheng, Zheng, Feng, Zhang, & Xiao, ) in the diet might improve the weight reduction.…”
Section: Introductionmentioning
confidence: 99%
“…Lifestyle change including dietary interventions and physical activity is regarded as an inevitable part of obesity treatment strategies (Swift, Johannsen, Lavie, Earnest, & Church, ). Although reduced dietary energy intake is an important part of weight‐reducing diets, a number of studies have revealed that including functional foods like cinnamon, ginger, pepper, cumin, and garlic (Ebrahimzadeh Attari, Ostadrahimi, Asghari Jafarabadi, Mehralizadeh, & Mahluji, ; Gupta Jain, Puri, Misra, Gulati, & Mani, ; Szulinska et al, ; Zare, Heshmati, Fallahzadeh, & Nadjarzadeh, ; Zheng, Zheng, Feng, Zhang, & Xiao, ) in the diet might improve the weight reduction.…”
Section: Introductionmentioning
confidence: 99%
“…It also is a major compound of capsaicinoids (alkaloid) that are widely applied in pharmaceutical and clinical product [7]. As one of the natural products, it was reported that capsaicin has therapeutic properties currently employed as antitumor [8], anti-mutagenic [9], antioxidant compounds [7], antimicrobial [3], anticancer [10], cardio-protection [11], antiobesity [12], anti-diabetic [13], and antiinflammatory effect [14].…”
Section: Introductionmentioning
confidence: 99%
“…Chili peppers are common food flavoring, which are also used as a traditional medicine in some cultures [150,151]. Chilis contain pungent capsaicinoids (capsaicin and dihydro-capsaicin), the major bioactive compounds responsible for the hot taste sensation, non-pungent capsaicin analogs, named capsinoids (e.g., capsiate, dihydro-capsiate and nordihydro-capsiate); and antioxidants, vitamins and carotenoids [150].…”
Section: Chili Pepper (Capsicum Species) Available Evidencementioning
confidence: 99%